Alcohol consumption patterns and risk of HIV transmission among men who have sex with men living with HIV in Chongqing, southwestern China - Chen, Huailiang; Fan, Hui; Yang, Panhao; Luo, Yingxin; Chen, Jin (Frontiers in Public Health, 2025)
IntroductionThere has been limited research on alcohol consumption patterns and their specific risks for the transmission of human immunodeficiency virus (HIV) and sexually transmitted infections (STIs) among men who have sex with men (MSM) living with HIV. The aim of this study was to examine the effects of alcohol consumption patterns on antiretroviral treatment (ART) adherence and sexual risk-taking behaviors among MSM living with HIV in Chongqing, a municipality with the highest HIV prevalence among MSM in China.MethodsAn institutionally based cross-sectional survey was conducted between 2022 and 2023 in Chongqing, China. The Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) was administered to evaluate alcohol consumption patterns. Multivariate logistic regression analysis was employed to examine the associations between alcohol consumption patterns, ART adherence, and sexual risk-taking behaviors.ResultsOf the 1,501 MSM living with HIV, the prevalence of alcohol use, hazardous drinking, and binge drinking was 60.2, 24.9 and 43.6%, respectively. Multivariate logistic regression analysis revealed that alcohol use, hazardous drinking, and binge drinking were significantly associated with a higher likelihood of ART non-adherence (adjusted odds ratio [aOR] = 1.89, 95% confidence interval [CI]: 1.08–3.30; aOR = 3.43, 95% CI: 2.11–5.58; aOR = 2.17, 95% CI: 1.30–3.62), having multiple sex partners (aOR = 1.62, 95% CI: 1.27–2.06; aOR = 1.49, 95% CI: 1.11–1.99; aOR = 1.65, 95% CI: 1.29–2.11), engaging in commercial sex (aOR = 2.50, 95% CI: 1.56–3.99; aOR = 3.21, 95% CI: 2.16–4.75; aOR = 3.11, 95% CI: 2.03–4.75), and participating in group sex (aOR = 1.73, 95% CI: 1.05–2.83; aOR = 1.79, 95% CI: 1.14–2.80; aOR = 1.77, 95% CI: 1.12–2.80). Alcohol use and binge drinking were associated with higher odds of casual sex (aOR = 1.31, 95% CI: 1.03–1.66; aOR = 1.52, 95% CI: 1.18–1.95). Hazardous drinking and binge drinking were associated with condomless internal ejaculation (CIE) (aOR = 1.37, 95% CI: 1.03–1.83; aOR = 1.44, 95% CI: 1.11–1.86).ConclusionHigh levels of alcohol use, hazardous drinking, and binge drinking are observed among MSM living with HIV in Chongqing. Given the significant associations between alcohol consumption, ART non-adherence, and sexual risk-taking behaviors, public health strategies in Chongqing and similar settings may benefit from screening and interventions to address alcohol consumption among MSM living with HIV.